Comparative Literature Analysis of The Folklore Between Goa Mampu and Bowerman’s Nose - Jumaldin Irwansyah; Muh. Taufik; Nur Mutmainna Halim; Dahniar B (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
This research aims to: 1) identify the similarities and differences between the legend of Goa Mampu and Bowerman's Nose. 2) find out moral values behind the stories of Goa Mampu and Bowerman's Nose. The research method used in this research is the descriptive qualitative method. The researcher used a literature review to collect the data. The data obtained were folklore stories from the legend of Goa Mampu and the legend of Bowerman’s Nose. The data then analyzed by using the comparative literature method. The results of this research show that these two legends have similarities and differences. Similaritiy from two legends is only found in the minor theme both the legend of Goa mampu and Bowerman's Nose, told about curse and equivalence. On the other hand, differences from those two legends are found in the minor theme, major theme and in the background defiction of two legends. Goa Mampu’s minor theme was well-being, while Bowerman’s Nose’s minor theme was destiny of life. Meanwhile, Goa Mampu’s major theme was broken promises that lead to disaster, while Bowerman’s Nose’s major theme was errors culmination in punishments. Not only that, but the results of this research also found the moral value of the two legends. Namely, in the legend of Goa Mampu are 1) we shall be able to be independent and not to expect others. 2) think about everything before act, includ the spoken promises. 3) when we promise something, the promise must be fulfilled. And in the legend of Bowerman’s Nose are 1) in doing something we are required to have an introspective nature or be careful in our actions. 2) pay more attention to the surroundings while on the move. 3) what goes around, comes around. Keywords: Bowerman’s Nose, Comparative Literature, Folklore, Goa Mampu.